2017
DOI: 10.1210/jc.2017-00591
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Mini-Dose Glucagon for Treatment of Nonsevere Hypoglycemia in Adults With Type 1 Diabetes

Abstract: Low-dose glucagon can successfully treat mild hypoglycemia and may be a useful alternative to treatment with oral carbohydrate when trying to avoid unnecessary caloric intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 11 publications
2
32
0
1
Order By: Relevance
“…Nausea without vomiting has been reported infrequently after exposure to 150 mg of MDG (0 of 12 [15] and 3 of 17 [16] participants in previous studies), which is consistent with complaints in 2 of the 15 participants here. Although this is likely related to the established effect of glucagon to relax gastrointestinal smooth muscle (20), nausea occurred more often with a 300-mg dose of MDG (4 of 12 participants) (15) and is observed with or without vomiting in more than a third of individuals treated with 1-mg emergency doses of glucagon (21).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nausea without vomiting has been reported infrequently after exposure to 150 mg of MDG (0 of 12 [15] and 3 of 17 [16] participants in previous studies), which is consistent with complaints in 2 of the 15 participants here. Although this is likely related to the established effect of glucagon to relax gastrointestinal smooth muscle (20), nausea occurred more often with a 300-mg dose of MDG (4 of 12 participants) (15) and is observed with or without vomiting in more than a third of individuals treated with 1-mg emergency doses of glucagon (21).…”
Section: Discussionsupporting
confidence: 90%
“…A nonaqueous liquid form of glucagon is currently in development with appropriate dose-dependent pharmacokinetic and pharmacodynamics responses when administered subcutaneously at doses of 75, 150, and 300 mg in adults with type 1 diabetes (15). A recent study demonstrated that 150 mg of this mini-dose glucagon (MDG) product was as effective as oral glucose tablets in correcting nonsevere hypoglycemia in adults with type 1 diabetes, enabling the avoidance of unnecessary caloric intake (16). In the current study, we sought to determine whether MDG given subcutaneously before aerobic exercise could prevent subsequent glucose lowering in adults with type 1 diabetes compared with no intervention and further to evaluate the glycemic responses seen with insulin reduction and glucose tablets approaches for mitigating exercise-associated hypoglycemia.…”
mentioning
confidence: 99%
“… 11 Mini-doses of glucagon are effective in treating mild to moderate hypoglycemic episodes in both children 6 36 as well as adults. 16 …”
Section: Discussionmentioning
confidence: 99%
“…The split total glucagon dose was delivered every 10 min during the 60 min exercise sessions. Mini-doses of glucagon were found to be efficacious and safe to treat mild hypoglycemia in adults with type 1 diabetes [ 85 ]. Successful hypoglycemia-treatment criteria were met for 94% when using a mini-dose of glucagon in comparison to 95% when giving oral glucose tablets.…”
Section: Future Directionsmentioning
confidence: 99%